Performance of Governor System on Minimizing Frequency Fluctuations with Wind Power Generation - Sheikh, Dr. Md. Rafiqul Islam; Haque, Md. Mejbaul; Hossain, M.A. (International journal of electrical and computer engineering (Malacca, Malacca), 2012)
As wind turbine output is proportional to the cube of wind speed, the wind turbine generator output fluctuates due to wind speed variations. Hence, if the power capacity of wind power generators becomes large, wind power generator output can have an influence on the power system frequency. Therefore, this study investigates the influence of governor control systems of synchronous generators (SGs) for minimizing frequency fluctuations with high wind power penetration level, when a total capacity of SGs is considered as 100 MVA. It is seen that when both SGs operate as governor free (GF) operation, system perform better frequency control. But it can not be maintained to the acceptable level when SGs operate at GF-LFC or LFC-GF operation with wind power capacity about 5% of total capacity. Finally, it is seen that when several interconnected SGs are operated with different control modes, system frequency become more severe for 10% capacity of wind power.